Iatrogenic aortopulmonary communications after transcatheter interventions on the right ventricular outflow tract or pulmonary artery: Pathophysiologic, diagnostic, and management considerations. Issue 3 (16th March 2015) - Torres, Alejandro; Sanders, Stephen P.; Vincent, Julie A.; El‐Said, Howaida G.; Leahy, Ryan A.; Padera, Robert F.; McElhinney, Doff B.
<x xml:space="preserve">Abstract</x> Objectives To investigate the spectrum, etiology, and management of traumatic aortopulmonary (AP) communications after transcatheter interventions on the pulmonary circulation. Background An iatrogenic AP communication is an unusual complication after balloon pulmonary artery (PA) angioplasty or stenting, or transcatheter pulmonary valve replacement (TPVR). However, with the increasing application of transcatheter therapies for postoperative PA stenosis and right ventricular outflow tract (RVOT) dysfunction, including percutaneous pulmonary valve replacement, consideration of the etiology, diagnosis, and management of this problem is important for interventional cardiologists performing such procedures. Methods and Results We present three new cases, as well as gross anatomy and histopathology data, related to AP communications after PA interventions. We also review the literature relevant to this topic. Including these new cases, there have been 18 reported cases of iatrogenic AP communication after transcatheter interventions on the PAs or RVOT, primarily patients with transposition of the great arteries who underwent PA angioplasty after an arterial switch operation, or after TPVR in patients who had undergone a Ross procedure. The likely cause of such defects is PA trauma plus distortion of the neo‐aortic anastomosis resulting from angioplasty or stenting of the RVOT or central PAs, with subsequent dissection through the extravascular connective tissue and into the closely adjacent vessel through the devitalized tissue at the anastomosis. Conclusions Cardiologists performing PA or RVOT interventions should be aware of the possibility of a traumatic AP communication and consider this diagnosis when confronted with suggestive signs and symptoms. © 2015 Wiley Periodicals, Inc.